Incentive travel as an effective employee motivator in South Africa - Hollis, Adrian (My University, 2011)
The purpose of this study was to determine whether travel incentive schemes are an effective way to motivate employees and improve their productivity in South African based companies. A questionnaire was administered to employees of four companies which operated an incentive travel program. The results of the questionnaire were discussed with key managers at each of the four companies. The main findings of the research were that whilst the majority of employees surveyed would prefer a cash incentive if given the choice, the travel incentive is an effective method to motivate employees. The research also confirmed that incentive travel schemes have a number of unique benefits that make this type of incentive more attractive to management than a cash incentive.
MBA - WBS
Keywords: Motivation; Incentive schemes; Employee motivation